A standardised approach towards selecting forests for strict protection in Germany - Patricia Borel; Jan-Geert Bliefernicht; Eva Flinkerbusch; Martin Gutsch; Anke Höltermann; Ulrich Matthes; Mats Nieberg; Tobias Nowakowski; Max Tölle; Christopher P. O. Reyer (Regional Environmental Change, 2026)
Forests serve as key ecosystems for biodiversity conservation and climate change mitigation. The achievement of ambitious biodiversity targets, such as the EU Biodiversity Strategy’s target of strictly protecting 10% of the EU’s land area, requires the systematic identification of key forest areas for protection. However, clear guidance on selecting such forests is lacking. In this study, we address this issue by developing forest protection scenarios based on different conservation criteria and data from the third German National Forest Inventory. We used state-of-the-art indicators capturing different aspects of biodiversity: forest structure, habitat conservation, legal protection status, and the presence of old forests, alongside sociopolitical considerations including public ownership and equal distribution across federal states. Using a standardised, multi-criteria approach, we systematically identified forest areas for strict protection that best complied with each scenario’s criteria. Each scenario was then tested against three targets: strictly protecting 5%, 10%, and 30% of the total forest area. Our analysis revealed that, despite the application of different selection criteria in each scenario, the characteristics of the forests ultimately selected showed only moderate differences. Achieving higher protection targets, such as 10% or 30%, required including stands with lower conservation value, as evidenced by lower criterion overlap within selected forest areas. Although existing forest habitat types with no or minimal management requirements (i.e. 15.24% of German forest area) could theoretically serve as the selection pool for the 5% and 10% targets, sociopolitical considerations, such as having an equal spread of protected areas across federal states, required the incorporation of other forest areas. Overall, our findings provide a foundation for implementing Germany’s and the EU’s strict nature protection targets and demonstrate that multiple pathways exist to achieve them. However, strategic compromises may be required as the goals become more ambitious.

Insights into the mineralogy and distribution of Co, Ni, As and Bi in the sediment-hosted polymetallic ores of the Kupferschiefer in Lusatia, Germany - Zahra Nourizenouz; Max Frenzel; Bradley Martin Guy; Aratz Beranoaguirre; Jens Gutzmer (Journal of Geochemical Exploration, 2026)

Hadean components preserved in Paleo- to Neoarchean rocks from the Yilgarn Craton, W-Australia - Max Hellers; Jonas Tusch; Carina Gerritzen; Eric Hasenstab-Dübler; Mario Fischer-Gödde; Andreas R.A. Schneider; Chris S. Marien; Josua J. Pakulla; R. Hugh Smithies; Martin J. Van Kranendonk; Dieter Garbe-Schönberg; Carsten Münker (Earth and Planetary Science Letters, 2026)

Reframing Green Prosperity: integrating sustainability and just transitions into Community Wealth Building - Max Lacey-Barnacle; Ed Atkins; Eleanor Radcliffe; Martin Boucher (Environmental Innovation and Societal Transitions, 2026)

Emerging tools to advance neuroethology in butterflies and moths - Francesco Cicconardi; Max S. Farnworth; Robin Grob; Donya N. Shodja; Caroline N. Bacquet; Basil el Jundi; Arnaud Martin; Stephen H. Montgomery (Journal of Comparative Physiology A, 2026)
Butterflies and moths have played historically important roles in developing our understanding of both ecology and evolutionary biology, and neuroethology. In both contexts, the diversity of behavioral strategies and specializations displayed by different Lepidoptera make them informative case studies. However, as in neuroscience more broadly, lepidopteran neuroethology has tended to focus on intricate functional studies within a small number of the most tractable species. In contrast, ecologists and evolutionary biologists have often taken a broader view, using phylogenetic and comparative approaches to extract general patterns of diversification, and to exploit the diversity of butterflies and moths to understand general evolutionary processes. Uniting these approaches and traditions has been restricted, largely due to technical challenges of working with unestablished study systems and a lack of resources beyond basic tools. Now, however, the prospects for broader comparative studies of the neural basis of behavior within a phylogenetic and/or ecological framework are increasingly positive. This is in large part due to the emergence of new molecular sequencing approaches and associated tools. These allow for the survey of cell types, the spatial location of their soma, development of new cell-type markers for targeted analyses, and quantification of the dynamic regulation of gene expression at a tissue or cell specific level. Results of these molecular methods can be combined with technical developments in free flying behavioral experiments in tethered animals that permit neural recordings of natural behavior, and functional genetics tools that can allow for more precise manipulation of these behaviors or the neural structures that support them. Here, we review these new approaches, their potential application, and discuss how we can use them to advance the development of new, integrative systems for studying the neural basis of behavior in butterflies and moths.

Oh deer, what are you? differentiating white-tailed and mule deer post-cranial skeletons - Max Kremer; Martin H. Welker (Archaeological and Anthropological Sciences, 2026)

Reduction of micron-sized iron oxide particles with high initial porosity in a fluidized bed reactor using hydrogen: Morphology and phase analysis - Malte Seitz; Martin P. Kannengießer; Björn Stelzner; Fabian P. Hagen; Lukas Braun; Jonas Kaltenbach; Kerstin Märkle; Martin Peterlechner; Jonas Spielmann; Dmitry E. Doronkin; Max P. Deutschmann; Jan-Dierk Grunwaldt; et al. (Fuel, 2026)

The deportment of silver in Kupferschiefer ores at the Spremberg-Graustein-Schleife deposit, Germany - Zahra Nourizenouz; Bradley Martin Guy; Jens Gutzmer; Doreen Ebert; Ralph Braumann; Max Frenzel (Mineralium Deposita, 2026)
The high-grade stratabound copper ores of the Central European Kupferschiefer are one of the world’s most important sources of silver. Despite its economic significance, the mineralogical partitioning of silver within the Kupferschiefer ores is generally not well understood, other than the fact that silver minerals are not sufficiently abundant to account for the bulk of the silver content. This study provides the first fully quantitative silver deportment for Kupferschiefer-type ores, using the Spremberg-Graustein-Schleife project in Germany as a case study. Our comprehensive analytical approach integrates scanning electron microscope (SEM)-based automated mineralogy and electron probe micro-analysis (EPMA) on exploration drill-core samples collected from different host rocks and different metal tenor. The results were validated using bulk geochemical data, and uncertainties were assessed with Monte Carlo simulations. The results demonstrate that the majority of the silver within high-grade Cu-rich ores occurs as a trace constituent in the ore-forming Cu(-Fe) sulfides (chalcocite group minerals, covellite, bornite, and chalcopyrite). In samples containing little copper, however, Fe sulfides host the majority of the silver in the form of micro-inclusions within copper-enriched crystal growth zones and substitution within the crystal lattice. The close association of copper and silver has important implications for ore genesis and mineral processing. These implications may well transfer to other by-products and other examples of polymetallic sediment-hosted copper mineral systems.

Perspectives: State of national forest damage survey programmes in Europe and ways toward improved harmonization and data sharing - Tomáš Hlásny; Michaela Perunová; Roman Modlinger; Max Blake; Gediminas Brazaitis; György Csóka; Maarten de Groot; Mihai-Leonard Duduman; Massimo Faccoli; Margarita Georgieva; Georgi Georgiev; Wojciech Grodzki; et al. (Forest Ecology and Management, 2025)

Functionality of duplicated cd9 paralogous antiviral genes in salmonids - Max Charles Vallarino; Victoria A. Sleight; Bertrand Collet; Pierre Boudinot; Samuel A.M. Martin (Fish & Shellfish Immunology, 2025)

Stream Degradation: Direct and Indirect Impacts of Amazonian Deforestation - Gabriel Martins Cruz; Ana Paula Justino Faria; Josinete Sampaio Monteles; Karina Dias-Silva; Lilian Casatti; Juan Mateo Rivera-Perez; Rafael Costa Bastos; Victor Rennan Santos Ferreira; Leandro Schlemmer Brasil; Thaisa Sala Michelan; Lenize Batista Calvão; Everton Cruz da Silva; et al. (Ecosystems, 2025)

Relationships of Anemia, Serum Iron, and Serum Copper in Hospitalized Alpacas (Vicugna pacos) - Max Kornblum; Johannes Buchallik-Schregel; Petra Röhrig; Antje Polifka; Martin Ganter; Matthias Gerhard Wagener (Biological Trace Element Research, 2025)
A large number of South American camelids (SAC) presented to a veterinary clinic are diagnosed with anemia. While various causes are known, such as infections with Haemonchus contortus , chronic inflammation, neoplasia, gastric ulcers, or deficiencies, little is known about the role of the trace elements copper and iron in SAC. In this retrospective study, the laboratory diagnostic data, in particular the red and white blood count, as well as the findings of the initial clinical examination of 181 alpacas presented at the University of Veterinary Medicine Hannover, Hannover, Germany in the period from January 2020 to September 2023 were therefore analyzed. In addition, iron, copper, transferrin, and ceruloplasmin were determined in the serum collected during the initial examination. The statistical analysis revealed significant correlations between the serum iron content and various degrees of anemia, and also between serum copper content and various degrees of anemia. These observations confirm the need to characterize the iron metabolism of SAC more precisely to improve differentiation between different causes of anemia.

Epiphytic lichens in old castle parks in Southwest Germany: A case study - Max Zibold; Martin Weckesser; Markus Scholler (Urban Ecosystems, 2025)

Cellular senescence—from solid organs to vascularized composite allotransplants - Leonard Knoedler; Andreas Schroeter; Jasper Iske; Jillian Dean; Sam Boroumand; Thomas Schaschinger; Tobias Niederegger; Samuel Knoedler; Adriana C. Panayi; Max Heiland; Stefan G. Tullius; Bohdan Pomahac; et al. (GeroScience, 2025)
Vascularized composite allotransplantation (VCA) has emerged as a novel therapy approach to restore form and function in patients with severe tissue defects of the face, hand, and abdominal wall, among other anatomical regions. The composite allografts comprise different tissues such as skin, muscle, or bone. Clinical data demonstrate promising mid- and long-term outcomes following VCA surgery, but our understanding of the cellular interactions and molecular pathways in VCA surgery is oftentimes deduced from solid organ transplantation (SOT). In SOT, the concept of cellular senescence has grown increasingly popular which is characterized by a permanent cellular proliferation arrest in response to endogenous and exogenous stimuli. Senescent cells, through the release of mitochondrial DNA and secretion of proinflammatory proteins, can amplify the immunogenicity of transplants, hindering graft acceptance and longevity. This understanding has paved the way for novel interventions, including the use of senolytics—agents that selectively eliminate senescent cells—to modulate immune responses and mediate immunotolerance. There is a body of evidence that underlines the therapeutic potential of senescence to improve SOT outcomes; however, the relevance of senescence to VCA outcomes remains elusive. In this review, we aim to summarize the current literature on senescence in different solid organ transplants and outline the potential impact of senescence on VCA outcomes. This knowledge may help providers develop a broader understanding of the cellular and molecular landscape in VCA to develop targeted therapies and advance VCA patient care.

Serum Iron and Its Relationship with Hematologic Parameters in Healthy Female Alpacas at Two Different Ages - Matthias Gerhard Wagener; Max Kornblum; Frederik Kiene; Martin Ganter; Ulrike Teichmann (Biological Trace Element Research, 2025)
Iron is an important trace element whose deficiency is associated with anemia, which is a common condition in South American camelids. However, there are only few data available on the physiologic relationships between serum iron and hematologic findings in alpacas. In 81 laboratory diagnostic datasets from 21 clinically healthy alpacas collected over a nine-year period, we recently reported significant positive correlations between iron and hemoglobin (Hb), hematocrit (HCT), mean corpuscular volume (MCV), mean corpuscular hemoglobin (MCH), and eosinophils, and significant negative correlations between iron and mean corpuscular hemoglobin concentration (MCHC), platelets, and neutrophils. For 11 of the animals, datasets were available both at the age of 1 year (young) and at an older age (4–7 years: mature). For young animals, significant positive correlations were found between iron and MCV, MCH, and eosinophils, and significant negative correlations between iron and white blood cells (WBC), red blood cells (RBC), platelets, and neutrophils. In contrast, in mature animals, significant positive correlations were found between iron and monocytes as well as eosinophils. A two-way ANOVA of these 11 animals examining the effects of age, iron, and age*iron revealed significant effects of age on eosinophils, of iron on RBC and MCH, and of age*iron on WBC, RBC, HCT, and lymphocyte-to-monocyte ratio (LMR). Our data show that both age and serum iron have an effect on hematologic parameters in alpacas. Especially in young animals there is a close association between iron and MCH and MCV and neutrophils.

Two sides of the coin: Feedback-driven landscape formation results in trade-off between establishment and resilience of marram grass - Solveig Höfer; Lissie de Groot; Nathan Scanlan; Eva Lansu; Max Rietkerk; Martin Wassen; Tjisse van der Heide; Valérie C. Reijers (Oecologia, 2025)
Habitat-modifying plants engineer biogeomorphic landscapes through self-reinforcing interactions with their physical environment, or so-called ‘biogeomorphic feedbacks’. Nevertheless, benefits can vary across a biogeomorphic landscape gradient and between plant-life stages. For instance, European marram grass forms dunes by trapping sediments which triggers plant growth, in turn promoting sediment trapping. Yet, by increasing dune height and vegetation cover, marram grass mitigates sediment dynamics, inhibiting sediment-growth feedbacks, which ultimately leads to its demise. However, little is known about how dune formation affects the growth and survival of marram grass at different life stages. Therefore, we performed a two-level field experiment testing the effect of position on marram grass across the biogeomorphological dune gradient (beach, foredune, backdune) on (i) the establishment success of juvenile transplants and (ii) the resilience of mature plants to disturbance by above-ground biomass removal, over one growing season. Although juvenile transplants grew similarly well across the dune gradient, significantly fewer beach transplants (67%) survived compared to the foredune- and backdune transplants. Conversely, survival of mature disturbed marram grass (100%) was unaffected, yet recovery was highest at the beach and significantly decreased across the dune gradient. We could link these opposing responses to habitat modification. In heavily modified dune habitats sediment stabilization aided juvenile establishment, whereas the high sediment dynamics of unmodified beaches facilitated adult resilience indicating dune formation invokes a trade-off between establishment and resilience. Our findings highlight the importance of assessing life stage-dependent differences in environmental requirements of habitat-modifying plants to understand population dynamics and landscape-forming processes.

Odonata Diversity and Ecological Thresholds in Protected Areas of the Brazilian Amazon - Kenned Silva Sousa; Joás Silva Brito; Gabriel Martins Cruz; Rafael Costa Bastos; Cristian Camilo Mendoza-Penagos; Everton Silva; Luciano Montag; José Max Barbosa Oliveira-Junior; Gabriel Brejão; Lilian Casatti; Thaísa Sala Michelan; Leandro Juen; et al. (Neotropical Entomology, 2025)

Impact of absolute values and changes in meteorological and air quality conditions on community-acquired pneumonia in Germany - Saeed A. Khan; Thomas Brenner; Ann-Christine Link; Christoph Reudenbach; Jörg Bendix; Barbara C. Weckler; Max Kutzinski; Jan Rupp; Martin Witzenrath; Gernot Rohde; Mathias W. Pletz; Wilhelm Bertrams; et al. (International Journal of Biometeorology, 2025)
Community-acquired pneumonia (CAP) is a major global health concern as it is a leading cause of morbidity, mortality and economic burden to the health care systems. In Germany, more than 15,000 people die every year from CAP. Climate change is altering weather patterns, and it may influence the probability and severity of CAP. The increasing frequency and intensity of extreme weather events necessitate the study of their impact on CAP hospitalizations. In this regard, we examine the influence of absolute values and changes in various meteorological and air quality conditions on the frequency of CAP hospitalizations. We matched weather data to the German CAPNETZ-Cohort of 10,660 CAP patients from 22 healthcare facilities between 2003 and 2017. Our findings show that daily fluctuations in meteorological conditions (maximum temperature, 99th percentile precipitation), apart from relative humidity, are likely to result in triggering CAP hospitalizations than absolute conditions. In contrast, the absolute values of air quality (CO, NO 2 , O 3 , PM 2.5 , SO 2 , and total aerosols) are found to exert a greater influence on CAP hospitalizations than changes in air quality. The study outcomes have implications for public health measures, early warning systems, and public awareness, with the aim of mitigating the risk of CAP.

Structural health monitoring (SHM) on a long semi-integral high-speed railway bridge (HSRB) under different traffic loads - Sisi Zhang; Max Käding; Marc Wenner; Martin Claßen; Steffen Marx (Engineering Structures, 2025)

Species and site contributions to Odonata adult assemblage uniqueness in Brazilian Amazon streams - Ana Caroline Leal-Nascimento; André Ribeiro-Martins; Karina Dias-Silva; Leandro Juen; Amanda Frederico Mortati; José Max Barbosa Oliveira-Junior (Journal of Insect Conservation, 2025)

Dashboard for interpreting future climate files used in the simulation of buildings – An outdoor thermal comfort approach - Igor Catão Martins Vaz; Enedir Ghisi; Liseane Padilha Thives; Abel Silva Vieira; Ricardo Forgiarini Rupp; Aline Schaefer; Rafael Almeida Flores; Matheus Bruhns Bastos; Deivis Luis Marinoski; Arthur Santos Silva; Max Weeber; Andrea Invidiata (Energy and Buildings, 2025)

Characterization of a primary cellular airway model for inhalative drug delivery in comparison with the established permanent cell lines CaLu3 and RPMI 2650 - Janik Martin; Rebecca Rittersberger; Simon Treitler; Patrick Kopp; Anit Ibraimi; Gabriel Koslowski; Max Sickinger; Annabelle Dabbars; Katharina Schindowski (In vitro models, 2024)
Purpose For optimization of respiratory drug delivery, the selection of suitable in vitro cell models plays an important role in predicting the efficacy and safety of (bio)pharmaceutics and pharmaceutical formulations. Therefore, an in-depth comparison of different primary and permanent in vitro cellular airway models was performed with a focus on selecting a suitable model for inhalative antibodies. Methods Primary cells isolated from the porcine trachea were compared with the established human cell lines CaLu3 and RPMI 2650. The in vitro models were characterized for different epithelial markers by real-time quantitative polymerase chain reaction, which provides insight into the cellular composition of each model. For a few selected markers, the results from RT-qPCR were confirmed via immunofluorescence. Barrier integrity was assessed by transepithelial electrical resistance measurements and FITC-dextran permeability. Results Primary cell models retain key features of the respiratory epithelium, e.g., the formation of a tight epithelial barrier, mucin production, and the presence of club/basal cells. Furthermore, the expression of Fc receptors in the primary cell models closely resembles that in respiratory mucosal tissue, an essential parameter to consider when developing therapeutic antibodies for inhalation. Conclusion The study underlines the importance of selecting wisely appropriate in vitro models. Despite the greater effort and variability in cultivating primary airway cells, they are far superior to permanent cells and a suitable model for drug development.

Insights into fluid evolution and Re enrichment by mineral micro-analysis and fluid inclusion constraints: Evidence from the Maronia Cu-Mo ± Re ± Au porphyry system in NE Greece - Jan J. Falkenberg; Manuel Keith; Vasilios Melfos; Max Hohl; Karsten M. Haase; Panagiotis Voudouris; Alica Höss; Julia Wenske; Reiner Klemd; Christoph Beier; Martin Kutzschbach; Harald Strauss (Mineralium Deposita, 2024)
Porphyry-epithermal veins hosting Re-rich molybdenite and rheniite (ReS 2 ) from the Maronia Cu-Mo ± Re ± Au porphyry in Thrace, NE Greece, provide new insights into the hydrothermal processes causing extreme Re enrichment. Quartz trace element chemistry (Al/Ti, Ge/Ti), Ti-in-quartz thermometry, and cathodoluminescence imaging reveal multiple quartz generations in consecutive hydrothermal quartz-sulfide veins associated with potassic, sericitic, and argillic alteration. Fluid inclusions in different quartz generations indicate that phase separation and fluid cooling are the main ore-forming processes in the porphyry stage (~ 500 – 350 °C), whereas mixing of a vapor-rich fluid with metalliferous (e.g., Pb, Zn, Au) meteoric water forms the epithermal veins (~ 280 °C). These processes are recorded by trace element ratios in pyrite that are sensitive to changes in fluid temperature (Se/Te), fluid salinity (As/Sb, Co/As), and mixing between fluids of magmatic and meteoric origin (Se/Ge). Highly variable intra-grain δ 34 S values in pyrite record S isotope fractionation during SO 2 disproportionation and phase separation, emphasizing the importance of in situ δ 34 S analysis to unravel ore-forming processes. High δ 34 S (~ 4.5‰) values of sulfides are indicative of low SO 4 2− /H 2 S fluid ratios buffered by the local host rocks and mixing of the magma-derived fluid with meteoric water. The formation of Re-rich molybdenite (~ 6600 ppm) is favored by cooling and reduction of a magma-derived, high-temperature (~400 °C), oxidized, and Re-rich fluid triggering efficient Re precipitation in early veins in the potassic alteration zone. The systematic temporal fluid evolution therefore reveals that coeval cooling and reduction of oxidized Re-rich fluids cause extreme Re enrichment at the Maronia porphyry system.

Serpentinization as the source of energy, electrons, organics, catalysts, nutrients and pH gradients for the origin of LUCA and life - Loraine Schwander; Max Brabender; Natalia Mrnjavac; Jessica L.E. Wimmer; Martina Preiner; William F. Martin (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Ferredoxin reduction by hydrogen with iron functions as an evolutionary precursor of flavin-based electron bifurcation - Manon L. Schlikker; Max Brabender; William F. Martin (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Assessment of body mass-related covariates for rifampicin pharmacokinetics in healthy Caucasian volunteers - Muhammad Bilal; Sami Ullah; Ulrich Jaehde; Christina Trueck; Dario Zaremba; Bertil Wachall; Manfred Wargenau; Bernhard Scheidel; Martin H. J. Wiesen; Malaz Gazzaz; Chunli Chen; Sören Büsker; et al. (European Journal of Clinical Pharmacology, 2024)
Purpose Currently, body weight-based dosing of rifampicin is recommended. But lately, fat-free mass (FFM) was reported to be superior to body weight (BW). The present evaluation aimed to assess the influence of body mass-related covariates on rifampicin’s pharmacokinetics (PK) parameters in more detail using non-linear mixed effects modeling (NLMEM). Methods Twenty-four healthy Caucasian volunteers were enrolled in a bioequivalence study, each receiving a test and a reference tablet of 600 mg of rifampicin separated by a wash-out period of at least 9 days. Monolix version 2023R1 was used for NLMEM. Monte Carlo simulations (MCS) were performed to visualize the relationship of body size descriptors to the exposure to rifampicin. Results A one-compartment model with nonlinear (Michaelis–Menten) elimination and zero-order absorption kinetics with a lag time best described the data. The covariate model including fat-free mass (FFM) on volume of distribution (V/F) and on maximum elimination rate (Vmax/F) lowered the objective function value (OFV) by 56.4. The second-best covariate model of sex on V/F and Vmax/F and BW on V/F reduced the OFV by 51.2. The decrease in unexplained inter-individual variability on Vmax/F in both covariate models was similar. For a given dose, MCS showed lower exposure to rifampicin with higher FFM and accordingly in males compared to females with the same BW and body height. Conclusion Our results indicate that beyond BW, body composition as reflected by FFM could also be relevant for optimized dosing of rifampicin. This assumption needs to be studied further in patients treated with rifampicin.

Sampling completeness changes perceptions of continental scale climate–species richness relationships in odonates - Fernanda Alves‐Martins; Juliana Stropp; Leandro Juen; Richard J. Ladle; Jorge M. Lobo; Javier Martinez‐Arribas; Paulo De Marco Júnior; Leandro Schlemmer Brasil; Victor Rennan Santos Ferreira; Rafael Costa Bastos; Alex Córdoba‐Aguilar; Emmy Fiorella Medina‐Espinoza; et al. (Journal of Biogeography, 2024)
Aim Insects are one of the least studied taxa, with most species lacking basic ecological and biogeographical information. This problem is particularly acute in the tropics, where low sampling effort hampers accurate estimates of species richness at scale and potentially confounds efforts to identify the drivers of biogeographical gradients. Here, we evaluate the quality of the data on the distribution and diversity of odonate species in the Neotropics, while also examining the influence of sampling completeness on climate–richness relationships using a comprehensive database of odonates. Location The Neotropics. Taxon Odonata. Methods Using 56,535 records collected from 1970 to 2021, we assess whether climate–species richness models vary under different scenarios of survey completeness. Results Our survey compilation revealed that most Neotropical diversity of Odonata likely remains unknown. Only 1% of the one‐degree cells covering the Neotropics held reliable information on odonate species richness, with particularly severe gaps in the Caribbean, Central America, northeastern Brazil and northern Chile. Temperature, precipitation and potential evapotranspiration exert consistent effects on Odonata richness across the entire Neotropics, regardless the level of survey completeness. Whereas seasonality‐related variables are less important predictors of species richness at the biogeographical scale. Main Conclusions By highlighting areas where inventories are more reliable and identifying regions that require increased data collection efforts and mobilization, our assessment offers a roadmap for improving the reliability of odonate inventories in the Neotropics. Furthermore, our findings underscore the importance of accounting for varying levels of survey completeness in macroecological models to reveal robust climate–species richness relationships. Simultaneously, they highlight strong climatic predictors of species richness, irrespective of survey effort intensity. These predictors provide a solid foundation for modelling and predicting odonate species richness in the Neotropics.

Redox cycling of straw-amended soil simultaneously increases iron oxide crystallinity and the content of highly disordered organo-iron(III) solids - Christian Mikutta; Max Niegisch; Aaron Thompson; Ricarda Behrens; Laura S. Schnee; Martin Hoppe; Reiner Dohrmann (Geochimica et Cosmochimica Acta, 2024)

The importance of national parks in maintaining the habitat integrity and diversity of Odonata species in Amazonian streams - Joás Silva Brito; Everton Cruz Silva; Victor Rennan Santos Ferreira; Rafael Costa Bastos; Gabriel Martins Cruz; Josinete Sampaio Monteles; Adriana Lima; Marcelo Raseira; Gabriel Lourenço Brejão; José Max Barbosa Oliveira-Junior; Karina Dias-Silva; Thaisa Sala Michelan; et al. (Journal of Insect Conservation, 2024)

Contractional deformation between extensional dome exhumation in Central Pamir at 17–15 Ma constrained by metamorphic and paleomagnetic data from the Bartang volcanic rocks, Tajikistan - Jovid Aminov; Pierrick Roperch; Guillaume Dupont-Nivet; Carole Cordier; Stéphane Guillot; Johannes Glodny; Martin J. Timmerman; Masafumi Sudo; Gilles Ruffet; Max Wilke; France Lagroix; Ding Lin; et al. (Tectonophysics, 2023)

A study on the desulfurization of sulfidic mine tailings for the production of a sulfur-poor residue - Ana Luiza Coelho Braga de Carvalho; Victor Albuquerque de Carvalho; Rosie Blannin; Alexandra Gomez Escobar; Max Frenzel; Martin Rudolph; André Carlos Silva; Daniel Goldmann (Minerals Engineering, 2023)

The utility of using Volunteered Geographic Information (VGI) for evaluating pluvial flood models - Martin Drews; Max Steinhausen; Morten Andreas Dahl Larsen; Mads Lykke Dømgaard; Levente Huszti; Tibor Rácz; Michel Wortmann; Fred Fokko Hattermann; Kai Schröter (Science of The Total Environment, 2023)

A combined workflow to generate citywide building energy demand profiles from low-level datasets - Tong Guo; Max Bachmann; Mathias Kersten; Martin Kriegel (Sustainable Cities and Society, 2023)

The Martin moving grate technology - Ralf Koralewska; Ulrich Martin; Max Schönsteiner (Waste Disposal & Sustainable Energy, 2023)

Ecological ceiling and social floor: public support for eco-social policies in Sweden - Jamil Khan; Kajsa Emilsson; Martin Fritz; Max Koch; Roger Hildingsson; Håkan Johansson (Sustainability Science, 2023)
In this article, we investigate public support for eco-social policies combining goals of social justice and ecological sustainability. Eco-social policies contribute both to providing a social floor or redistributing resources to where they are needed and to respecting an ecological ceiling by keeping human activities within ecological limits. We discuss five such policies and highlight arguments for and against defining them as eco-social policies: a maximum income, a wealth tax, a basic income, a working time reduction and a meat tax. Asking what the social and individual determinants of supporting these policies are, we use 2020 data from a representative survey in Sweden containing information about how respondents evaluate the policies. We run regression analyses to estimate the effects on these evaluations and test for socio-economic, knowledge-based and value-based factors. Results show that (1) in Sweden a working time reduction is the most supported eco-social policy; (2) political left orientation increases support for all five eco-social policies; (3) socio-economic factors have effects on wealth tax, maximum income and working time reduction; and (4) knowledge-based factors are more associated with the meat tax. Thus, socio-economic and knowledge-based models have the most significance for policies that could be understood as being either social or environmental, while value-based models have significance across potentially perceived policy divides and hence to a greater extent explain support for policies targeting an ecological ceiling and a social floor.

Reservoir properties and reactivity of the Faroe Islands Basalt Group: Investigating the potential for CO2 storage in the North Atlantic Igneous Province - Marija P. Rosenqvist; Max W.J. Meakins; Sverre Planke; John M. Millett; Hans Jørgen Kjøll; Martin J. Voigt; Bjørn Jamtveit (International Journal of Greenhouse Gas Control, 2023)

Aerosol emissions from a marine diesel engine running on different fuels and effects of exhaust gas cleaning measures - Seongho Jeong; Jan Bendl; Mohammad Saraji-Bozorgzad; Uwe Käfer; Uwe Etzien; Julian Schade; Martin Bauer; Gert Jakobi; Jürgen Orasche; Kathrin Fisch; Paul P. Cwierz; Christopher P. Rüger; et al. (Environmental Pollution, 2023)

The relationship between executive functioning and addictive behavior: new insights from a longitudinal community study - Anja Kräplin; Mohsen Joshanloo; Max Wolff; Klaus-Martin Krönke; Thomas Goschke; Gerhard Bühringer; Michael N. Smolka (Psychopharmacology, 2022)
Rationale Although there is evidence that impaired executive functioning plays a role in addictive behavior, the longitudinal relationship between the two remains relatively unknown. Objectives In a prospective-longitudinal community study, we tested the hypothesis that lower executive functioning is associated with more addictive behavior at one point in time and over time. Methods Three hundred and thirty-eight individuals (19–27 years, 59% female) from a random community sample were recruited into three groups: addictive disorders related to substances ( n = 100) or to behaviors ( n = 118), or healthy controls ( n = 120). At baseline, participants completed nine executive function tasks from which a latent variable of general executive functioning (GEF) was derived. Addictive behavior (i.e., quantity and frequency of use, and number of DSM-5 criteria met) were assessed using standardized clinical interviews at baseline and three annual follow-ups. The trajectories of addictive behaviors were examined using latent growth curve modeling. Results At baseline, we found weak to no evidence of an associations between GEF and addictive behavior. We found evidence for an association between a lower GEF at baseline and a higher increase in the quantity of use and a smaller decrease in frequency of use over time, but no evidence for an association with an increase in the number of DSM-5 criteria met. Conclusions Lower EFs appear to lead to a continuing loss of control over use, whereas addictive disorders may develop secondarily after a long period of risky use. Previous etiological models assuming lower EF as a direct vulnerability factor for addictive disorders need to be refined.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Advances in Brazil Nut Tree Ecophysiology: Linking Abiotic Factors to Tree Growth and Fruit Production - Karen Cristina Pires da Costa; José Francisco de Carvalho Gonçalves; Alexandre Leão Gonçalves; Adamir da Rocha Nina Junior; Roberto Kirmayr Jaquetti; Vinícius Fernandes de Souza; Josiane Celerino de Carvalho; Andreia Varmes Fernandes; Joelma Keith Rodrigues; Gleisson de Oliveira Nascimento; Lúcia Helena de O. Wadt; Karen A. Kainer; et al. (Current Forestry Reports, 2022)

Antigonon leptopus invasion is associated with plant community disassembly in a Caribbean island ecosystem - Maarten B. Eppinga; Elizabeth A. Haber; Luke Sweeney; Maria J. Santos; Max Rietkerk; Martin J. Wassen (Biological Invasions, 2022)
Invasions by non-native plant species are widely recognized as a major driver of biodiversity loss. Globally, (sub-)tropical islands form important components of biodiversity hotspots, while being particularly susceptible to invasions by plants in general and vines in particular. We studied the impact of the invasive vine A. leptopus on the diversity and structure of recipient plant communities on the northern Caribbean island St. Eustatius. We used a paired-plot design to study differences in species richness, evenness and community structure under A. leptopus -invaded and uninvaded conditions. Community structure was studied through species co-occurrence patterns. We found that in plots invaded by A. leptopus , species richness was 40–50% lower, and these plots also exhibited lower evenness. The magnitude of these negative impacts increased with increasing cover of A. leptopus . Invaded plots also showed higher degrees of homogeneity in species composition. Species co-occurrence patterns indicated that plant communities in uninvaded plots were characterized by segregation, whereas recipient plant communities in invaded plots exhibited random co-occurrence patterns. These observations suggest that invasion of A. leptopus is not only associated with reduced species richness and evenness of recipient communities in invaded sites, but also with a community disassembly process that may reduce diversity between sites. Given that A. leptopus is a successful invader of (sub-)tropical islands around the globe, these impacts on plant community structure highlight that this invasive species could be a particular conservation concern for these systems.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Fertilized graminoids intensify negative drought effects on grassland productivity - Kevin Van Sundert; Mohammed A. S. Arfin Khan; Siddharth Bharath; Yvonne M. Buckley; Maria C. Caldeira; Ian Donohue; Maren Dubbert; Anne Ebeling; Nico Eisenhauer; Anu Eskelinen; Alain Finn; Tobias Gebauer; et al. (Global Change Biology, 2021)
Droughts can strongly affect grassland productivity and biodiversity, but responses differ widely. Nutrient availability may be a critical factor explaining this variation, but is often ignored in analyses of drought responses. Here, we used a standardized nutrient addition experiment covering 10 European grasslands to test if full‐factorial nitrogen, phosphorus, and potassium addition affected plant community responses to inter‐annual variation in drought stress and to the extreme summer drought of 2018 in Europe. We found that nutrient addition amplified detrimental drought effects on community aboveground biomass production. Drought effects also differed between functional groups, with a negative effect on graminoid but not forb biomass production. Our results imply that eutrophication in grasslands, which promotes dominance of drought‐sensitive graminoids over forbs, amplifies detrimental drought effects. In terms of climate change adaptation, agricultural management would benefit from taking into account differential drought impacts on fertilized versus unfertilized grasslands, which differ in ecosystem services they provide to society.

Impulsive decision-making predicts the course of substance-related and addictive disorders - Anja Kräplin; Michael Höfler; Shakoor Pooseh; Max Wolff; Klaus-Martin Krönke; Thomas Goschke; Gerhard Bühringer; Michael N. Smolka (Psychopharmacology, 2020)
Background This study investigated whether patterns of impulsive decision-making (i) differ between individuals with DSM-5 substance use disorders (SUD) or non-substance-related addictive disorders (ND) and healthy controls, and (ii) predict the increase of SUD and ND severity after one year. Methods In a prospective-longitudinal community study, 338 individuals (19–27 years, 59% female) were included in one of three groups: SUD ( n = 100), ND ( n = 118), or healthy controls ( n = 120). Group differences in four impulsive decision-making facets were analyzed with the Bayesian priors: delay discounting (mean = 0.37, variance = 0.02), probability discounting for gains and for losses (each − 0.16, 0.02), and loss aversion (− 0.44, 0.02). SUD and ND severity were assessed at baseline and after 1 year ( n = 312, 92%). Predictive associations between decision-making and SUD/ND severity changes were analyzed with the Bayesian prior: mean = 0.25, variance = 0.016. Results Compared with controls, the SUD group displayed steeper delay discounting and lower probability discounting for losses; the ND group displayed lower probability discounting for losses (posterior probabilities > 98%). SUD symptom increase after 1 year was predicted by steeper delay discounting and lower loss aversion; ND symptom increase by lower probability discounting for losses and lower loss aversion (posterior probabilities > 98%). There was low evidence for predictive relations between decision-making and the quantity-frequency of addictive behaviours. Discussion Impulsive decision-making characterizes SUD and ND and predicts the course of SUD and ND symptoms but not the engagement in addictive behaviours. Strength of evidence differed between different facets of impulsive decision-making and was mostly weaker than a priori expected.

Combined Grazing and Drought Stress Alter the Outcome of Nurse: Beneficiary Interactions in a Semi-arid Ecosystem - Mart Verwijmeren; Christian Smit; Susana Bautista; Martin J. Wassen; Max Rietkerk (Ecosystems, 2019)

Subdividing the Holocene Series/Epoch: formalization of stages/ages and subseries/subepochs, and designation of GSSPs and auxiliary stratotypes - MIKE WALKER; Martin J. Head; John Lowe; Max Berkelhammer; Svante BjÖrck; Hai Cheng; Les C. Cwynar; David Fisher; Vasileios Gkinis; Antony Long; Rewi Newnham; Sune Olander Rasmussen; et al. (Journal of Quaternary Science, 2019)
The Holocene, which currently spans ~11 700 years, is the shortest series/epoch within the geological time scale (GTS), yet it contains a rich archive of evidence in stratigraphical contexts that are frequently continuous and often preserved at high levels of resolution. On 14 June 2018, the Executive Committee of the International Union of Geological Sciences formally ratified a proposal to subdivide the Holocene into three stages/ages, along with their equivalent subseries/subepochs, each anchored by a Global boundary Stratotype Section and Point (GSSP). The new stages are the Greenlandian (Lower/Early Holocene Subseries/Subepoch) with its GSSP in the Greenland NGRIP2 ice core and dated at 11 700 a b2k (before 2000 CE); the Northgrippian (Middle Holocene Subseries/Subepoch) with its GSSP in the Greenland NGRIP1 ice core and dated at 8236 a b2k; and the Meghalayan (Upper/Late Holocene Subseries/Subepoch) with its GSSP in a speleothem from Mawmluh Cave, north‐eastern India, with a date of 4250 a b2k. We explain the nomenclature of the new divisions, describe the procedures involved in the ratification process, designate auxiliary stratotypes to support the GSSPs and consider the implications of the subdivision for defining the Anthropocene as a new unit within the GTS.

Flavobacteria as secondary pathogens in carp suffering from koi sleepy disease - Mikolaj Adamek; Felix Teitge; Verena Jung‐Schroers; Max Heling; David Gela; Veronika Piackova; Martin Kocour; Dieter Steinhagen (Journal of Fish Diseases, 2018)
Koi sleepy disease ( KSD ) is a disease with increasing importance in global common carp aquaculture. Despite the fact that carp edema virus ( CEV ) is most likely the causative agent of KSD , the disease often presents itself as multifactorial with several parasites and bacteria species present on gills, skin or in internal organs. Therefore, in this study, we analysed and presented initial results on an interaction of flavobacteria and CEV in the development of clinical KSD in carp suffering from proliferative gill disease. We examined selected field samples from Germany and Hungary and confirmed the presence of CEV and flavobacteria co‐infections in subset of the samples. In several infection experiments, we studied the transfer and dynamics of both infections. Furthermore, we analysed which Flavobacterium species could be isolated from KSD ‐affected fish and concluded that Flavobacterium branchiophilum is a possible copathogen. Antibiotic treatment experiments showed that CEV seems to be the primary pathogen causing an insult to the gills of carp and by these enabling other pathogens, including F . branchiophilum , to establish co‐infections. Despite the fact that F . branchiophilum co‐infection is not required for the development of clinical KSD , it could contribute to the pathological changes recorded during the outbreaks.

Movement Patterns Differ between Sexes and Depend on Weather Conditions in the Butterfly Lycaena tityrus - Elisabeth Reim; Ingo Arnstedt; Isabel Barwisch; Max Baumgarten; Sascha Bock; Julia Eberspach; Julia Ellerbrok; Mulugeta Gebremeskel; Simon Küpper; Lukas Guth; Aninha Lassen; Letro Letro; et al. (Journal of Insect Behavior, 2018)

Residual rivaroxaban exposure after discontinuation of anticoagulant therapy in patients undergoing cardiac catheterization - Martin H. J. Wiesen; Cornelia Blaich; Max Taubert; Veronika Jennissen; Thomas Streichert; Roman Pfister; Guido Michels (European Journal of Clinical Pharmacology, 2018)

Ecological-Economic Fisheries Management Advice—Quantification of Potential Benefits for the Case of the Eastern Baltic COD Fishery - Rudi Voss; Martin F. Quaas; Max T. Stoeven; Jörn O. Schmidt; Maciej T. Tomczak; Christian Möllmann (Frontiers in Marine Science, 2017)

Analysis of FOXP3+ regulatory T cell subpopulations in peripheral blood and tissue of patients with systemic lupus erythematosus - Angelika Schmidt; Cosima C. Rieger; Ram Kumar Venigalla; Szabolcs Éliás; Regina Max; Hanns-Martin Lorenz; Hermann-Josef Gröne; Peter H. Krammer; Annegret Kuhn (Immunologic Research, 2017)

Changes in kelp forest biomass and depth distribution in Kongsfjorden, Svalbard, between 1996–1998 and 2012–2014 reflect Arctic warming - Inka Bartsch; Martin Paar; Stein Fredriksen; Max Schwanitz; Claudia Daniel; Haakon Hop; Christian Wiencke (Polar Biology, 2016)

Temporal shift in biomass and production of macrozoobenthos in the macroalgal belt at Hansneset, Kongsfjorden, after 15 years - Martin Paar; Andrey Voronkov; Haakon Hop; Thomas Brey; Inka Bartsch; Max Schwanitz; Christian Wiencke; Benoit Lebreton; Ragnhild Asmus; Harald Asmus (Polar Biology, 2016)

Response to conspecific chemical cues in surface- and cave-dwelling populations of Atlantic mollies, Poecilia mexicana - Jonas Jourdan; Max Jordan; Claudia Zimmer; Constanze Eifert; Lenin Arias-Rodriguez; Martin Plath (Environmental Biology of Fishes, 2016)

Using an isolated population boom to explore barriers to recovery in the keystone Caribbean coral reef herbivore Diadema antillarum - Max D. V. Bodmer; Alex D. Rogers; Martin R. Speight; Natalie Lubbock; Dan A. Exton (Coral Reefs, 2015)

History and Origin of Russet Burbank (Netted Gem) a Sport of Burbank - Paul C. Bethke; Atef M. K. Nassar; Stan Kubow; Yves N. Leclerc; Xiu-Qing Li; Muhammad Haroon; Teresa Molen; John Bamberg; Max Martin; Danielle J. Donnelly (American Journal of Potato Research, 2014)

Conditional loss of kidney microRNAs results in congenital anomalies of the kidney and urinary tract (CAKUT) - Malte P. Bartram; Martin Höhne; Claudia Dafinger; Linus A. Völker; Marc Albersmeyer; Julia Heiss; Heike Göbel; Hella Brönneke; Volker Burst; Max C. Liebau; Thomas Benzing; Bernhard Schermer; et al. (Journal of Molecular Medicine, 2013)

Insight to Ecosystem Based Approach (EBA) at Landscape Level Using a Geospatial Medium - Nidhi Nagabhatla; Sonali S. Sellamuttu; A. Ghosh Bobba; Max Finlayson; Rohan Wickramasuriya; Martin Van Brakel; S. Narendra Prasad; Chiranjibi Pattanaik (Journal of the Indian Society of Remote Sensing, 2012)

Facies and provenance of basin-margin deposits in the Los Palacios Basin (Capdevila Formation, Cuba) - Juliane Brust; Heiko Hüneke; Martin Meschede; Max Sommer (Facies, 2011)

Resource contrast in patterned peatlands increases along a climatic gradient - Maarten B. Eppinga; Max Rietkerk; Lisa R. Belyea; Mats B. Nilsson; Peter C. De Ruiter; Martin J. Wassen (Ecology, 2010)
Spatial patterning of ecosystems can be explained by several mechanisms. One approach to disentangling the influence of these mechanisms is to study a patterned ecosystem along a gradient of environmental conditions. This study focused on hummock–hollow patterning of peatlands. Previous models predicted that patterning in drainage‐dominated peatlands is driven by a peat‐accumulation mechanism, reflected by higher nutrient availability in hollows relative to hummocks. Alternatively, patterning in evapotranspiration (ET)‐dominated peatlands may be driven by a nutrient‐accumulation mechanism, reflected by reversed nutrient distribution, namely, higher nutrient availability in hummocks relative to hollows. Here, we tested these predictions by comparing nutrient distributions among patterned peatlands in maritime (Scotland), humid temperate (Sweden), and humid continental (Siberia) climates. The areas comprise a climatic gradient from very wet and drainage‐dominated (Scotland) to less wet and ET‐dominated (Siberia) peatlands. Nutrient distribution was quantified as resource contrast, a measure for hummock–hollow difference in nutrient availability. We tested the hypothesis that the climatic gradient shows a trend in the resource contrast; from negative (highest nutrient availability in hollows) in Scotland to positive (highest nutrient availability in hummocks) in Siberia. The resource contrasts as measured in vegetation indeed showed a trend along the climatic gradient: contrasts were negative to slightly positive in Scotland, positive in Sweden, and strongly positive in Siberia. This finding corroborates the main prediction of previous models. Our results, however, also provided indications for further model development. The low concentrations of nutrients in the water suggest that existing models could be improved by considering both the dissolved and adsorbed phase and explicit inclusion of both nutrient‐uptake and nutrient‐storage processes. Our study suggests that future climate change may affect the ecosystem functioning of patterned peatlands by altering the contribution of pattern‐forming mechanisms to redistribution of water and nutrients within these systems.

Investigation of LDHA and COPB1 as candidate genes for muscle development in the MYOD1 region of pig chromosome 2 - Haifang Qiu; Xuewen Xu; Bing Fan; Max F. Rothschild; Yerle Martin; Bang Liu (Molecular Biology Reports, 2010)

Linking habitat modification to catastrophic shifts and vegetation patterns in bogs - Maarten B. Eppinga; Max Rietkerk; Martin J. Wassen; Peter C. De Ruiter (Plant Ecology, 2009)

Regular Surface Patterning of Peatlands: Confronting Theory with Field Data - Maarten B. Eppinga; Max Rietkerk; Wiebe Borren; Elena D. Lapshina; Wladimir Bleuten; Martin J. Wassen (Ecosystems, 2008)

The Effects of Spatial Scale on Trophic Interactions - Johan Van de Koppel; Richard D. Bardgett; Janne Bengtsson; Claudino Rodriguez-Barrueco; Max Rietkerk; Martin J. Wassen; Volkmar Wolters (Ecosystems, 2005)

The significance of European high mountain lakes in critical load distributions at the EMEP grid scale - Chris J. Curtis; Max Posch; Pilar Casals-Carrasco; Jordi Catalan; Mike Hughes; Martin Kernan; Marc Ventura (Aquatic Sciences, 2005)

The significance of European high mountain lakes in critical load distributions at the EMEP grid scale - Chris J. Curtis; Max Posch; Pilar Casals-Carrasco; Jordi Catalan; Mike Hughes; Martin Kernan; Marc Ventura (Aquatic Sciences, 2005)

Evaluation of tuber-bearingSolanum species for nitrogen use efficiency and biomass partitioning - Mohamed Errebhi; Carl J. Rosen; Florian I. Lauer; Max W. Martin; John B. Bamberg (American Journal of Potato Research, 1999)

Fine screening potato (Solanum) species germplasm for tuber calcium - J. B. Bamberg; J. P. Palta; L. A. Peterson; Max Martin; A. R. Krueger (American Journal of Potato Research, 1998)

Screening of exotic potato germplasm for nitrogen uptake and biomass production - Errebhi Mohamed; Carl J. Rosen; Florian I. Lauer; Max W. Martin; John B. Bamberg; David E. Birong (American Journal of Potato Research, 1998)

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)

Screening tuber-bearingSolanum (potato) germplasm for efficient accumulation of tuber calcium - J. B. Bamberg; J. P. Palta; L. A. Peterson; Max Martin; A. R. Krueger (American Journal of Potato Research, 1993)